Characterization of Cysteine Coated Magnetite Nanoparticles as MRI Contrast Agent - Ahmadi, Reza; Gu, Ning; Hosseini, Hamid Reza Madaah (Nano-Micro Letters, 2012)
In this work, a kind of stabilized ferrofluid based on magnetite nanoparticles (mean core and its coating size about 21.9 and 1.6 nm, respectively) was synthesized via coprecipitation method. Cysteine was used as surfactant due to its proper conjunction to the surface of magnetite nanoparticles. Coating density and synthesized ferrofluids were characterized by using transmission electron microscope, thermogravimetry analysis, dynamic light scattering and fourier transform infrared spectroscopy techniques. Magnetic resonance imaging studies show that the synthesized ferrofluid can be used as a potential contrast enhancement agent especially for imaging lymphatic system.